Functional Starch and Applications in Food - Jin, Zhengyu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book discusses functional starch and its applications in food, focusing on starches with possible health benefits or novel applications. Covering slowly digested starch, resistant starch, porous starch, starch microemulsions, microcrystalline starch and noncrystallization starch and their applications, this book provides a valuable reference for graduate students and research professionals in the food and chemical industries. .
Introduction -- Slowly digested starch and applications -- Resistant starch and applications -- Porous starch and applications -- Starch microemulsion and applications -- Microcrystalline starch and noncrystallization starch and their applications -- Starch‐lipid and starch‐protein complex and their applications.
Keywords: Food science; Biochemistry; Food Science; Biochemistry